Caracterização da incidência e evolução de pragas e doenças em agroecossistemas cafeeiros sob diferentes manejos - Lopes, Paulo Rogério (2009)
This research aims to characterize the incidence and development of major pests and diseases of coffee in agroecosystems under conventional, organicmineral, organic and agroforestry managements in two municipalities in the southern Minas Gerais State: Machado and Poço Fundo. It was carried out monthly monitoring of the leaf-miner (Leucoptera coffeella), borer coffee (Hypothenemus hampei), rust (Hemileia vastatrix) and brown eye spot (Cercospora coffeicola) for a period of one year (december/2007 the november/2008) in crops of Novo Mundo variety with spacing (3.0 to 3.5 m X 1.0 to 1.2 m). The monitoring of leaf-miner and diseases of the coffee was done through the collection of ten sheets of the third or fourth pair in all sides of the coffee, and twenty plants sampled by agroecosystem, totaling two hundred leaves collected for evaluation of pests and diseases in each system. To monitorate the borer coffee it was selected 32 plants, six different points on each plant (10 fruits grouped by set point) and there was non-destructive evaluation. In all agroecosystems monitored, both managed by the family farm, the infestation of the borer coffee and leaf-miner did not reach level of economic damage in any evaluation. With respect to diseases evaluated, it was observed that the rust and brown eye spot reached the level of economic damage in all management systems. However, the organic-mineral systems, organic (monoculture) and agroforestry (organic) the occurrence of rust was critical to reach high levels in the months april to october of 2008, and the values above 60% of incidence in four months of evaluation. The incidence of brown eye spot was relatively lower in the conventional and organic (monoculture), whose peaks did not exceed 41% and 55%, consecutively. Already in the organicmineral and agroforestry (organic) the occurrence of Cercospora reached very high levels, reaching 76% and 67% respectively in July. Despite the high incidence of rust and brown eye spot found in coffee agroecosystems organicmineral and organic, the average productivity achieved by these systems in the past three years was higher than the conventional, even the latter system investing heavy in pesticides and chemical fertilizers.